HAKIKAT INTERPRETASI MUHAMMAD SYAHRUR TENTANG POLIGAMI DAN RELEVANSINYA DENGAN HUKUM PERKAWINAN NASIONAL - wati, anda (AL-RISALAH, 2016)
This reseach discusses "The essence ofthe interpretation of Muhammad SyahrÅ«rabout Polygamy and its relevance to theNational Marriage lawâ. This study aimsto determine the concept of polygamyaccording to Mohammed SyahrÅ«r,methods Muhammad SyahrÅ«r inunderstanding the verses on polygamydanrelevansi concept of polygamyMuhammad SyahrÅ«r with nasioanlmarriage law.